2019
DOI: 10.1186/s12912-019-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Nurse career mapping: a qualitative case study of a new hospital

Abstract: Background Career mapping is an effective strategy for providing nurses with a clear direction and a realistic time scale for achieving their career goals. The purpose of this research is to investigate career mapping for nurses at a new hospital in Jakarta. Method The study design is qualitative and implements a focussed case study approach. Data were collected from focus group discussions (FGDs) with two groups: one group consisted of eight staff nurses and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 22 publications
1
15
1
1
Order By: Relevance
“…In contrast, in other studies such as "Nurse manager competencies", the focus is on the degree to which the competencies contribute to the nurse manager's work (minimally, moderately, significantly and essentially) [48]. Furthermore, the results of the current study emphasize the need for a high level of competence development, in the same way that Crawford et al [64] demonstrated by indicating how executive practice would require a high degree of specialization and a specific development of competencies.…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast, in other studies such as "Nurse manager competencies", the focus is on the degree to which the competencies contribute to the nurse manager's work (minimally, moderately, significantly and essentially) [48]. Furthermore, the results of the current study emphasize the need for a high level of competence development, in the same way that Crawford et al [64] demonstrated by indicating how executive practice would require a high degree of specialization and a specific development of competencies.…”
Section: Discussioncontrasting
confidence: 63%
“…Meanwhile, in public health centers, the bureaucracy is not placed within the institution, yet it is being handled by the district or city health offices. A study by Sandehang et al (2019) stated that the implementation of nursing career paths begins from mapping, working experience, and then assessing self and competency. As mentioned in Decree No.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it is not only institutions that take the responsibility toward the change itself but also the individuals, especially nurses, who have the intention of taking part in career development. A qualitative research on nursing career mapping found that nursing officers or managers needed to provide a position suitable to the individual's competency (Sandehang et al, 2019). Holt et al (2010) stated that individual readiness to change is divided into two factors, including structural and psychological factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations